Perlindungan Hukum Bagi Pelapor Tindak Pidana Korupsi (Whistleblower) oleh Lembaga Perlindungan Saksi dan Korban (LPSK) Berdasarkan Undang-Undang Nomor 31 Tahun 2014 - Sujana, Ahmad; Kania, Dede; Anwar, Syahrul (Universitas Pahlawan Tuanku Tambusai, 2025)
Corruption is an extraordinary crime that has negative impacts on various aspects of life, including the economy, public trust, and government stability. Efforts to combat corruption in Indonesia have been carried out through various policies and regulations, including Law Number 31 of 1999 jo. Law Number 20 of 2001 on the Eradication of Corruption. One important instrument in supporting the eradication of corruption is the involvement of the public in reporting corrupt acts through a whistleblowing mechanism. This research aims to analyze the implementation of legal protection for whistleblowers in Indonesia based on Law Number 31 of 2014 on the Protection of Witnesses and Victims, particularly in providing protection for whistleblowers. In addition, the study examines the implementation of whistleblower protection policies and improving the effectiveness of legal protection for whistleblowers in corruption cases. This research uses a normative juridical method with a statute approach to analyze regulations that govern protection for whistleblowers, especially Law Number 31 of 2014, as well as policies implemented by Lembaga Perlindungan Saksi dan Korban (LPSK) and other law enforcement agencies. Data analysis is conducted using a qualitative analysis method. Based on the research findings, it is concluded that legal protection for whistleblowers still faces various challenges in its implementation. Normatively, legal protection for whistleblowers is regulated under Law Number 31 of 2014, but policy reforms are needed to strengthen the role of LPSK in providing more comprehensive protection for whistleblowers. With a more effective legal protection system, it is hoped that whistleblowers will be able to play a larger role in the fight against corruption, thereby promoting the creation of a more transparent, accountable, and integral legal system in Indonesia.